Alternative dispute resolution in art-related cases - Gwoździewicz-Matan, Paulina (Problemy Prawa Prywatnego Międzynarodowego, 2018)
One of the features of so called “art cases” is that the solutions are rarely black and white, therefore conventional remedies such as damages are often not adequate. Choosing alternative methods, widely recommended by international organizations, permits parties to reach creative non monetary solutions. The article aims at discussing how non-judicial methods are used in art cases and whether they are better for solving art related disputes. The first part of this article describes the methods that are used in particular cases, the formation of ADR clauses and also refers to the institutional rules of conduct. The second part lists the arguments for using ADR methods in art cases.